(untitled) (Eurasian Journal of Ecology, 2016)
Biophysical peculazities of rabbit auricular biologically active points under the influence of noise in a special apparatus that detects noise had been studied in normal conditions and experience. Changes had been noticed exposure to noise and oscillation the rate of chronostructural parameters was changed. The temperature of biologically active points in the animals were have two groups division.